2009
DOI: 10.1088/0004-637x/702/1/249
|View full text |Cite
|
Sign up to set email alerts
|

Luminous Red Galaxy Halo Density Field Reconstruction and Application to Large-Scale Structure Measurements

Abstract: The nontrivial relationship between observations of galaxy positions in redshift space and the underlying matter field complicates our ability to determine the linear theory power spectrum and extract cosmological information from galaxy surveys. The Sloan Digital Sky Survey (SDSS) luminous red galaxy (LRG) catalog has the potential to place powerful constraints on cosmological parameters. LRGs are bright, highly biased tracers of largescale structure. However, because they are highly biased, the nonlinear con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 45 publications
4
66
0
Order By: Relevance
“…(15) overestimates the beat-coupling effect. This conclusion agrees with a recent study of Reid, Spergel & Bode (2008), where they showed that the simulation results are fairly well explained if Eq. (15) reduced by a factor 3 is added to the Gaussian covariance.…”
Section: Effects Of Long-wavelength Fluctuationssupporting
confidence: 93%
“…(15) overestimates the beat-coupling effect. This conclusion agrees with a recent study of Reid, Spergel & Bode (2008), where they showed that the simulation results are fairly well explained if Eq. (15) reduced by a factor 3 is added to the Gaussian covariance.…”
Section: Effects Of Long-wavelength Fluctuationssupporting
confidence: 93%
“…Thus they are frequently used as an efficient tracer of large scale structure. Furthermore, since the LRGs have been shown to live in the most massive haloes of the Universe [10,28,29,63], they can be effectively probed with our N -body simulations.…”
Section: Reference Samplementioning
confidence: 99%
“…While some such studies have been performed (see e.g. [24,25]), a systematic study, leading to a complete and well tested analytic description has until now been lacking.…”
Section: Introductionmentioning
confidence: 99%